Hurt to Healing: Exploring Forgiveness in Female Friendships - Nawaz, Fizza; Haroon, Zara (Pakistan Journal of Humanities and Social Sciences, 2025)
Friendship plays a crucial role in emotional well-being by offering companionship, support, and a sense of belonging. However, conflicts can emerge within closely knit friendships, leading to profound emotional distress and resentment, hence challenging one’s ability to forgive and heal. The study explores the process of forgiveness within the context of close female friendships, focusing on the emotional entanglements and challenges involved in this journey. Using a qualitative narrative research inquiry, six participants were recruited through a purposive sampling technique, engaging in semi-structured, in-depth interviews to gain deeper insights. Thematic analysis revealed six major themes including (a) Multifaceted nature of forgiveness, emphasizing the non-linear process of forgiveness; (b) anchors in female friendships including unconditional trust, emotional attachment and powerful shared memories; (c) breaking points in female friendships like betrayal, bullying, manipulation, hurt expectations and toll on self-esteem; (d) barriers to forgiveness like conflicted emotions, continuous remuneration, fear of recurrence, societal influence and unresolved confrontation; (e) coping strategies ranging from distraction techniques and religious guidance to social support and lastly (f) healing through forgiveness, offering inner peace, closure, personal growth and transformation in self-esteem. The findings offer insight into how forgiveness in female friendships is not only an interpersonal but also an intrapersonal act driven by a sense of self, memories, and adaptability. The study implies interventions to nurture emotional regulation, restoration, and enduring relationships among youth.